HUBUNGAN ANTARA PENGETAHUAN KESEHATAN GIGI DENGAN NILAI INDEKS DMF-T SISWA SEKOLAH MENENGAH PERTAMA - M. Fahrul Ryzanur.A; Widodo Widodo; Rosihan Adhani (Dentin, 2022)
ABSTRACTBackground: The prevalence of people with oral and dental problems in Indonesia according to Riskesdas in 2018 was 57.6% with the National DMF-T index of 7.1. Lack of knowledge about oral and dental health causes a person not knowing the causes and prevention of dental caries. Purpose: To determine the results of published studies related to the relationship between dental health knowledge and the DMF-T index value of junior high school students. Method: A literature review with the type of narrative literature review. Data collection is carried out through electronic media. The data source is Secondary data from journals regarding the relationship between dental and oral health knowledge on the DMF-T score of junior high school students. Results: The results of the review of 12 journals conducted, found that the largest average percentage of DMF-T from 6 journals was in the low category, which was 27.45%, the average percentage of the largest dental and oral health knowledge level of the 5 journals was in the good / high, which is equal to 57.68%. Conclusion: There is a relationship between the level of knowledge and the DMF-T index, most of the DMF-T index tends to be low in students with high levels of knowledge. Keywords: DMF-T index, Junior high school students, Level of knowledge. ABSTRAKLatar Belakang: Prevalensi masyarakat yang bermasalah gigi dan mulut di Indonesia menurut Riskesdas tahun 2018 sebesar 57,6% dengan indeks DMF-T Nasional sebesar 7,1%. Pengetahuan yang kurang mengenai kesehatan gigi dan mulut menyebabkan seseorang tidak mengetahui penyebab dan pencegahan karies gigi. Tujuan: Untuk mengetahui hasil penelitian yang sudah dipublikasikan yang berkaitan dengan hubungan pengetahuan kesehatan gigi dengan nilai indeks DMF-T siswa SMP. Metode: Literature review menggunakan jenis narrative literature review. Pengumpulan data dilakukan melalui media elektronik. Sumber data berupa data sekunder dari jurnal mengenai hubungan pengetahuan kesehatan gigi dan mulut terhadap nilai DMF-T siswa SMP. Hasil: Hasil review 12 jurnal yang dilakukan, ditemukan rata-rata persentase DMF-T terbesar dari 6 jurnal pada kategori rendah, yaitu sebesar 27,45%, rata-rata persentase tingkat pengetahuan kesehatan gigi dan mulut terbesar dari 5 jurnal tersebut adalah pada kategori baik/tinggi, yaitu sebesar 57,68%. Kesimpulan: Terdapat hubungan tingkat pengetahuan dengan indeks DMF-T, sebagian besar indeks DMF-T cenderung rendah pada siswa dengan tingkat pengetahuan tinggi. Kata kunci: Indeks DMF-T, Siswa SMP, Tingkat pengetahuan.